2021
DOI: 10.1021/acsanm.1c01215
|View full text |Cite
|
Sign up to set email alerts
|

Au/N-Doped Carbon Dot Nanozymes as Light-Controlled Anti- and Pro-Oxidants

Abstract: Disturbances in the redox state of a biological system can cause diverse effects and clinical functions. The key and difficulty lies in controlling the balance between reduction and oxidation. Nanomaterials with oxidoreductase-like activity offer an appealing way to adjust antiand pro-oxidation in response to biological conditions. To this end, we design and prepare visible light-responsive hybrid nanozymes by combining Au and N-doped carbon dots (Au/NC). It is found that Au/NC can efficiently scavenge reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…The radicals are responsible for the strong fluorescence emissions centered at 435 nm in the absence of Au/NC, while the emission was reduced in the presence of a catalyst. 118 Furthermore, the synthesis methods can significantly influence the activity of the nano-carbon nanozymes. Herein, Dong et al synthesized the enzyme-like CDs (e-CDs) via the solvothermal method in N , N -dimethylformamide (DMF).…”
Section: Designs and Advancement In Nano-carbon Based Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The radicals are responsible for the strong fluorescence emissions centered at 435 nm in the absence of Au/NC, while the emission was reduced in the presence of a catalyst. 118 Furthermore, the synthesis methods can significantly influence the activity of the nano-carbon nanozymes. Herein, Dong et al synthesized the enzyme-like CDs (e-CDs) via the solvothermal method in N , N -dimethylformamide (DMF).…”
Section: Designs and Advancement In Nano-carbon Based Nanozymesmentioning
confidence: 99%
“…The mechanism was studied by the generation of • OH with the help of Fenton reagent. The radicals are responsible for the strong fluorescence emissions centered at 435 nm in absence of Au/NC while the emission was reduced in presence of catalyst 118. Further, the synthesis methods can also significantly influence the activity of nano-carbon nanozymes.…”
mentioning
confidence: 99%
“…Another recent study using Au gold carbon nano dots (Au/NC) was reported by Zhao et al The Au/NC prepared exhibited superoxide dismutase (SOD) like activity and depleted reactive oxygen species and free radicals in dark. However, on irradiation with visible light, the same Au/NC enhanced the generation of HO·, O 2 − , 1 O 2 and catalyzed the oxidation reactions ( Zhao et al, 2021 ). Thus, smart quantum dots can be designed to induce cell protective and cytotoxic activities, which can be controlled by a light switch.…”
Section: Semiconductor Quantum Dotsmentioning
confidence: 99%
“…The enzymatic properties of CDs are considerably improved through the formation of hybrids with other materials (e.g., Au, Pd, Fe 3 O 4 , Mn 3 O 4 , and CeO 2 ) [24][25][26][27]. Metal ions (e.g., Mn and Fe) with multiple oxidation states promote the enzymatic activity of CDs [28][29][30][31]. The simple addition of metal ions and chelate molecules to the reaction solution accelerates the enzymatic activity of CDs at a neutral pH [32].…”
Section: Introductionmentioning
confidence: 99%
“…The simple addition of metal ions and chelate molecules to the reaction solution accelerates the enzymatic activity of CDs at a neutral pH [32]. Doping metal species into a CD framework can act as a catalase mimic and reduce oxidative-stress-related damage on CDs by decomposing H 2 O 2 to H 2 O and O 2 [28]. Metal ions can also influence the formation of CDs and induce variations in the chemical structure of CDs during their synthesis, leading to the enhancement of physicochemical properties [29].…”
Section: Introductionmentioning
confidence: 99%